Finerenone in diabetic kidney disease: a new frontier for slowing disease progression - Alhomoud, Ibrahim S.; Albekery, Mohamed A.; Alqadi, Razan; Alqumia, Amal; Khan, Riaz A.; Al Sahlawi, Muthana; Al Mulhim, Mohammed Yousef (Frontiers in Medicine, 2025)
Diabetic kidney disease (DKD) represents a substantial health burden for patients with type 2 diabetes mellitus (T2DM), markedly increasing morbidity and mortality. The cornerstone of DKD treatment remains renin-angiotensin system (RAS) blockade and risk factor control, such as blood pressure management, glycemic control, albuminuria reduction, and lipid management. However, treatment strategies have expanded to include sodium-glucose cotransporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists, which have proven effective in slowing kidney disease progression when combined with RAS inhibitors. Finerenone, a non-steroidal mineralocorticoid receptor antagonist (MRA), represents a novel approach to the management of DKD. It offers unique pharmacokinetic and pharmacodynamic properties compared with steroidal MRAs such as spironolactone and eplerenone. This review addresses the evolving landscape of diabetic kidney disease management, with a focus on finerenone’s distinct pharmacologic properties, structural characteristics, and clinical implications.